2018
DOI: 10.1542/hpeds.2017-0220
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model for Enhanced Prediction and Understanding of Unplanned 30-Day Pediatric Readmission

Abstract: Our model provides significant performance improvements in the prediction of unplanned 30-day pediatric readmissions with AUC higher than the LACE readmission model and other general unplanned 30-day pediatric readmission models. The model is expected to provide an opportunity to capture 39% of readmissions (at a selected operating point) and may therefore assist clinicians in reducing avoidable readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…We provide an assessment of model performance with recommendations on the potential implementation of the corresponding predictive models in the ED. The new variables we considered include several measures of current and past healthcare resource utilization that have been found to be associated with the related problem of hospital readmission [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…We provide an assessment of model performance with recommendations on the potential implementation of the corresponding predictive models in the ED. The new variables we considered include several measures of current and past healthcare resource utilization that have been found to be associated with the related problem of hospital readmission [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, a recent study on a pediatric population presented a promising prediction model with an area under the receiver operating characteristic curve (AUC) of 0.79. 8 There has been a growing interest in measuring gait speed for assessing motor function and long-term mortality. 9 It is thought to be a surrogate marker for frailty, and has even been called a new vital sign.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to assume that patients at greater risk for short-term readmission may also be at increased risk for hospitalization over a longer time frame [22]. The type and extent of surgery is known to affect readmission rate [5, 7], as is length of stay during a hospitalization [14, 23]. Auger and Davis found that patients admitted on a weekend were more likely to be readmitted within 30 days [10].…”
Section: Discussionmentioning
confidence: 99%